2013
DOI: 10.2215/cjn.00750113
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy in CKD

Abstract: SummaryBackground Cardiac resynchronization therapy (CRT) confers morbidity and mortality benefits to selected patients with heart failure. This systematic review examined effects of CRT in CKD patients (estimated GFR [eGFR] ,60 ml/min per 1.73 m 2 ).Design, setting, participants, & measurements MEDLINE and Scopus (from 1990 to December 2012) and conference proceedings abstracts were searched for relevant observational studies and randomized controlled trials (RCTs). Studies comparing the following outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 44 publications
(64 reference statements)
1
27
0
Order By: Relevance
“…Similarly, there was a significant improvement in LVEF with CRT in CKD patients (mean difference 6.24%). Subgroup analysis of 3 randomized clinical trials reported lower rates of death or hospitalization for HF with CRT in the CKD population [23].…”
Section: Heart Failure Renal Function and Crtmentioning
confidence: 97%
“…Similarly, there was a significant improvement in LVEF with CRT in CKD patients (mean difference 6.24%). Subgroup analysis of 3 randomized clinical trials reported lower rates of death or hospitalization for HF with CRT in the CKD population [23].…”
Section: Heart Failure Renal Function and Crtmentioning
confidence: 97%
“…Worse renal function was also associated with worse long-term prognosis after CRT. Despite this, a systematic review by Garg et al 18 demonstrated that CRT in patients with CKD led to an improvement in left ventricular ejection as well as GFR. More studies are required to evaluate this further; however, this suggests a degree of reversibility in cardiorenal syndromes 1 and 2.…”
Section: Cardiac Resynchronisationmentioning
confidence: 99%
“…However, data on the effect of CRT in patients with severe renal dysfunction are scarce (5). Major CRT clinical trials excluded patients with severe renal dysfunction and only two small retrospective studies described the effect of CRT in this group of patients (5,10,11).…”
Section: Effect Of Crt On Renal Function In Patients With Severementioning
confidence: 99%
“…Unfortunately, there are no data regarding CRT response among patients with CKD stage 4 to compare with. The limited reverse remodeling capacity of the myocardium after CRT in these patients may be caused by a chronic damage on the basis of uremic toxins, calcium/phosphate abnormalities, and hypervolemic damage (water and sodium retention) that could lead to myocardial fibrosis, capillary rarefraction, and endothelial cell dysfunction (5,7,13,(33)(34)(35). Probably concomitant conditions, such as anemia, increased levels of catecholamines, activated renin-angiotensin-aldosterone system resulting in increased myocardial fibrosis, fluid retention, and increased afterload, might represent other important factors to limit the favorable effect of CRT in cardiac function (35).…”
Section: Effect Of Crt On Renal Function In Patients With Severementioning
confidence: 99%
See 1 more Smart Citation